A comunicação radiofônica e a interação com estudantes do EJA em Mirassol D'Oeste - Santos, Maria Elizangela Goes dos (2018)
The research object selected for the present study is focused on audience perception of radio broadcast programming, more precisely on how groups of listeners, students from a class of Adult and Young Adult Continuing Education (EJA), held at a Public State School named Benedito Cesário da Cruz, interact with local programming from three (Hertzian wave) radio stations situated in Mirassol D’Oeste, Mato Grosso (CentralWestern) State, Brazil. Over the past years, it has been openly stated that traditional mass media, such as Hertzian radio broadcasting, have been drastically dropping in audience preference. The main argument under this current discourse is that a large number of interlocutors have been migrating from traditional Hertzian wave radio broadcasting to hypermedia – the latter, enhanced by new technologies such as computers and cell phone devices. This research work is aimed to investigate how the participants of the research group would produce interaction and interactivity, mediated by local radio broadcast programming. The research databases were generated in a three-phased methodological procedure. Firstly, a qualitative interview was carried out with radio presenters from each of the three local radio stations, aiming at finding out some relevant information regarding their content production, as well as identifying how the selected research participants would interact with the local programming. The second phase of the research involved other data collection tool – a questionnaire meant to build a profile of the participants and also to identify their personal characteristics and audience preferences to fit for research purposes. As for the survey response rate, 88 (eighty-eight) participants spontaneously replied the questionnaire. The outcomes from this research action provided samples for the quantitative data analysis. Finally, on the third stage of the work, a qualitative research, framed for focus group sessions and based on a free-association method (GASKELL, 2002) was conducted with two groups from EJA education: one consisting of eight (08) students, varying from 19 to 25, tagged as “Young Adults”. The other group of students, between the age of 30 and 45 years-old, were categorized as “Adults” and counting on nine (09) members, making a total of seventeen (17) volunteer participants. As previously stated, the main aim of this research was to identify through student-listener narratives which contents are mediated, and which ones are evidentiated through listener’s daily discursive practices. In other words, the research work was designed to investigate which contents effectively trigger the meaning-making process and are able to build social bonds, with basis on interaction and interactivity constructed from broadcast programming, which are provided by the three traditional radio broadcasting stations in Mirassol D’Oeste town.